A study on language in advertising slogans by two fast-food competitors Mcdonald versus Burger King = Nghiên cứu ngôn ngữ khẩu hiệu quảng cáo của hai đấu thủ nhà hàng thức ăn nhanh Mcdonald và Burger King - Đỗ, Thị Thu Hà (2021)
Advertising language in general and slogan language in particular have drawn a great deal of attention from not only linguists so far, but marketers, copywriters and even psychologists as well. Therefore, the research initially aimed at providing sufficient knowledge about main aspects in language of advertising, and gradually in order to support the research topic, pointing out specific linguistic means used in advertising slogans. Next, the study also discussed an adoption of slogan language by two famous competitors in the global fast-food industry McDonald and Burger King through an analytical methodology to figure out the use rate of each linguistic means displayed on their advertising slogans, thus implying the similarity and difference in employing the most typical means for their strategies in the branding competition. Besides, the research investigation involved the participation of a group of students who undertook questionnaire and interview on their advertising perception and evaluation on the effectiveness of slogans by each brand. Eventually, according to major findings, such main features of advertising language as phonological, lexical and morphological, syntactic and lastly semantic levels were introduced, at which McDonald and Burger King presented their own marketing purposes on differentiated application of linguistic devices. In the long run, it is helpful to perceive the research as an actual case study to stimulate and promote an awareness and interest of students towards ESP (English for Specific Purposes) subject.